An Infant with Human Parechovirus Type 3 Infection with a Distinctive Rash on the Extremities. Issue 2 (3rd September 2012) - Shoji, Kensuke; Komuro, Hisako; Kobayashi, Yoshinori; Shike, Tatsuhiko; Funaki, Takanori; Katsuta, Tomohiro; Miyata, Ippei; Saitoh, Akihiko
<x xml:space="preserve">Abstract</x> Abstract: Human parechovirus type 3 (HPeV3) is known to cause sepsis‐like syndrome and meningoencephalitis in neonates and young infants. We herein report a neonatal case of sepsis‐like syndrome due to HPeV3 infection, diagnosed using polymerase chain reaction (PCR), with a distinctive erythematous rash present mainly on the soles and palms that helped in the diagnosis of the disease. Combining the unique characteristics of rash and confirmation by PCR at the early stage of the disease led to the diagnosis of HPeV3, distinguishing it from sepsis and other critical disease conditions, and allowing for appropriate, rapid management.